Microtubule integrity regulates budding yeast RAM pathway gene expression - Lee, Cameron Howard; Biggins, Sue (Frontiers in Cell and Developmental Biology, 2022)
During mitosis, cells must spatiotemporally regulate gene expression programs to ensure accurate cellular division. Failures to properly regulate mitotic progression result in aneuploidy, a hallmark of cancer. Entry and exit from mitosis is largely controlled by waves of cyclin-dependent kinase (CDK) activity coupled to targeted protein degradation. The correct timing of CDK-based mitotic regulation is coordinated with the structure and function of microtubules. To determine whether mitotic gene expression is also regulated by the integrity of microtubules, we performed ribosome profiling and mRNA-sequencing in the presence and absence of microtubules in the budding yeast Saccharomyces cerevisiae. We discovered a coordinated translational and transcriptional repression of genes involved in cell wall biology processes when microtubules are disrupted. The genes targeted for repression in the absence of microtubules are enriched for downstream targets of a feed-forward pathway that controls cytokinesis and septum degradation and is regulated by the Cbk1 kinase, the Regulation of Ace2 Morphogenesis (RAM) pathway. We demonstrate that microtubule disruption leads to aberrant subcellular localization of Cbk1 in a manner that partially depends on the spindle position checkpoint. Furthermore, constitutive activation of the RAM pathway in the absence of microtubules leads to growth defects. Taken together, these results uncover a previously unknown link between microtubule function and the proper execution of mitotic gene expression programs to ensure that cell division does not occur prematurely.